LEGAL INTERPRETATION OF THE PHRASES "RECOGNIZED" AND "ADJUSTED" IN THE TRANSITIONAL PROVISIONS OF HYPOTHEEK AND CREDIET VERBAND RELATED TO SECURITY RIGHTS: A STUDY ON THE HARMONIZATION OF COLONIAL AND NATIONAL LAND SECURITY SYSTEMS - Ompu Sunggu, Hengki; Santoso, Budi; Sulistyarini, Rachmi; Sri Kusuma Dewi, Amelia (REVISTA ESMAT, 2025)
This study aims to examine in depth the realization of the principle of legal certainty in the execution of material guarantees in the form of Mortgage and Crediet Verband on land and buildings after the enactment of Law No. 4 of 1996 on Mortgage (UUHT). The main focus of this study is the interpretation of the phrases “recognized” and “adjusted” in Article 24 paragraphs (1) and (2) of the UUHT, which have created legal issues due to the vagueness of the norm. This research employs a normative juridical and philosophical approach, analyzing the legal norms from ontological, epistemological, and axiological perspectives. The findings show that the lack of clarity regarding the norms of recognition and adjustment of old rights to the Mortgage system results in legal uncertainty in the execution practice by the security holders, especially banking institutions. This leads to difficulties in consistent implementation in legal practice, which risks undermining trust in the legal system in Indonesia. Therefore, this study recommends the need for clearer legal interpretation or norm reformulation to ensure legal certainty, justice, and effective legal protection for all involved parties, both creditors and debtors. This reformulation would strengthen the continuity of UUHT implementation and reduce uncertainties that could affect the effectiveness of the material guarantee law in Indonesia.